Understanding the effect of high-volume fly ash on micro-structure and mechanical properties of cemented coal gangue paste backfill. (16th May 2023) - Cheng, Yunhai; Shen, Hao; Zhang, Junfei
Highlights: The effect of high-volume fly ash on the microstructure and mechanical properties of CCGPB was studied. The importance of the influencing variables on the strength development was analyzed by an RF model. The maximum UCS was achieved at the mass concentration of 0.81 and the fly ash-cement replacement ratio of 0.42. The curing age had the highest relative importance (47.7%) on the UCS gain. Abstract: The utilization of coal gangue and fly ash to produce cemented paste backfill is an effective strategy to mitigate the environmental impact of such bulk solid wastes. In this study, we aimed to investigate the hardening properties of cemented coal gangue paste backfill (CCGPB) containing high-volume fly ash using macroscopic and microscopic characterization techniques. Specifically, uniaxial compressive strength (UCS) and slump were measured to evaluate the hardening properties of CCGPB, while Scanning Electron Microscopy (SEM) and Mercury Intrusion Porosimetry (MIP) were used to characterize the internal microstructure and internal pores. A total of 216 mixture proportions were designed through variations in the contents of cement, fly ash, water, and curing time. The resulting experimental data were used to develop a random forest model. This model was subsequently employed to evaluate the impact of different variables on the development of UCS in CCGPB. The results revealed that the slump increased with increasing fly ash contents and mass concentration. The maximum UCS was achieved at the mass concentration of 0.81 and the fly ash-cement replacement ratio of 0.42, which was also verified by the SEM showing a more compact interfacial transition zone with hydration products of calcium silicate hydrates, calcium aluminosilicate hydrates, and ettringites. The MIP results showed that the addition of fly ash had slight effect on the pores less than 1 μm, while pores larger than 1 μm increased with increasing fly ash content. The porosity ratio decreased by only 4% when fly ash was increased from 30% to 50%. The simulation results by the developed RF model indicated that the curing age had the highest relative importance (47.7%), while the UCS gain was less sensitive to the fly ash content compared with the cement. Overall, this study provides valuable insights into the application of fly ash and coal gangue to cemented paste backfill.